Visual Bias in Indonesian Platform-Based Journalism: Media Ownership and Instagram Coverage in Radar Cirebon - Muzadi, Akhmad (Asian Journal of Media and Communication, 2025)
This study examines how visual bias is articulated in local digital journalism by analysing Radar Cirebon’s Instagram coverage during the 2024 mayoral election in Cirebon, Indonesia. Employing a qualitative content analysis, eighty-two Instagram posts published during the official campaign period were examined using Denis McQuail’s framework of media performance, focusing on presentational features such as personalization, dramatization, stereotyping, juxtaposition, and accuracy. The findings reveal a consistent pattern of visual and textual alignment that favoured the media owner–affiliated candidate, expressed through evaluative captions, aesthetic personalization, and emotionally charged imagery. Rather than manifesting through explicit misinformation, bias operated at the level of representation and interpretation, shaped by both ownership structures and the platform logic of Instagram. Situated within debates on platformization and the political economy of media, the study highlights the particular vulnerability of local journalism in Indonesia, where close proximity between media ownership and political actors can blur editorial boundaries in digital contexts. By repositioning McQuail’s media performance framework within platform-based journalism, this research contributes to visual communication scholarship and underscores the need for stronger ethical safeguards to protect editorial independence in local digital media ecosystems.